Lessons learned from Minang Pelamin - Wesnina, .; Muhammad, Zikri (Opción, 2019)
This study analysed the pelamin as an artefact or cultural object from minang ethnic. Pelamin is the throne of adat leader in the inauguration and the bride in persandingan. By using description and interpretation approach to the concept of cultural objects as a symbol and meaning, this study examines design, decoration and altar in minang local knowledge. The results showed that the pelamin as cultural artefacts, not only has a traditional utility function, but also highlight a system of values, philosophy and worldview of minang culture that can be practically used in modern life of a human